2014
DOI: 10.1159/000357819
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Patients in Japan with Ovarian Cancer Presumably Arising from Ovarian Endometrioma

Abstract: Objective: To investigate the clinical features of patients in Japan with malignant transformation of ovarian endometrioma. Patients: Thirty-three patients diagnosed with ovarian cancer presumably arising from endometrioma were recruited retrospectively. These patients had been followed for at least 2 years after the ovarian endometrioma diagnosis, then continued to be followed after they had been found to have malignant transformation. Results: The average age of the patients was 47.7 ± 9.3 years; 75.7% were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 23 publications
1
22
1
Order By: Relevance
“…In our study, 50% of endometriosis-associated EOC cases were FIGO I-stage, and was also more common in low grade or borderline tumors. Several studies have reported a more benign character of the tumor when endometriosis is present [8,9,10,24,29,34,35] with better survival rates (as shown in fig. 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, 50% of endometriosis-associated EOC cases were FIGO I-stage, and was also more common in low grade or borderline tumors. Several studies have reported a more benign character of the tumor when endometriosis is present [8,9,10,24,29,34,35] with better survival rates (as shown in fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Ogawa et al [14] described 43 patients who had clear cell carcinoma and only 7 cases of endometrioid carcinoma, which confirms the great variability that is found in the histological classifications, both in the subtype of carcinoma and the subtype of endometriosis. But it has to be taken into account that the prevalence of clear cell EOC in Japan [34] seems to be much higher than that in western countries for unknown reasons. In our study, the few cases of atypical endometriosis that were associated with EOC were observed in endometrioid carcinomas, but no differences were observed between typical (with or without p53 expression) and atypical endometriosis in the clinical variables analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely accepted that type I tumors, in particular those of endometrioid and clear-cell histology, are strongly linked to endometriosis [9,10,11], which may involve the ovary after the implantation of endometrial fragments via retrograde menstruation. Several studies have raised the hypothesis of an ‘altered' endometrial cell to be considered the original precursor of type I ovarian tumors: it has already been found that the eutopic endometrium of those women affected by endometriosis is characterized by molecular alterations that may presumably allow the ‘altered' endometrial cell to spread toward ovarian tissue [11,12]. Consistent with this evidence is the higher rate of synchronous endometrial cancers found in patients with endometriosis-associated endometrioid ovarian carcinomas [9].…”
Section: Discussionmentioning
confidence: 99%
“…Primary epithelial tubo-ovarian cancer (ETOC) is a complex and heterogeneous group of tumors that remain the most deadly of all gynecologic malignancies [1]. Isolated recurrence in splenic parenchyma in patients with ETOC is extremely rare in the absence of apparent disease at other sites.…”
Section: Introductionmentioning
confidence: 99%